2009
DOI: 10.1007/s10560-009-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

Helping Families Initiative: Intervening with High-Risk Students through a Community, School, and District Attorney Partnership

Abstract: School-related violence and school infractions pose a significant problem for schools, families, and communities. This manuscript describes an effective community partnership and prevention effort operated by the District Attorney's office, in which high-risk students and their families were assessed, assigned case workers, and referred to community services. Findings indicated improved functioning across the duration of the program. Specifically, scores on the North Carolina Family Assessment Scale (NCFAS) im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Rozmi et al (2017) found that social environment factors were factors that contributed to substance abuse among adolescents. The results of this study have been supported by other studies of Turner et al (2009) and Rosser, Stevens and Ruiz (2005) which stated that school factors are an important medium in developing adolescent's behavior. This study also found that the behavioral abuse of substance occurs when environmentally risky factors such as accessible substance.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Rozmi et al (2017) found that social environment factors were factors that contributed to substance abuse among adolescents. The results of this study have been supported by other studies of Turner et al (2009) and Rosser, Stevens and Ruiz (2005) which stated that school factors are an important medium in developing adolescent's behavior. This study also found that the behavioral abuse of substance occurs when environmentally risky factors such as accessible substance.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Certainly, if attachment patterns continue to emerge as a risk factor for stalking and persistent unwanted pursuit, interventions may need to be more interpersonally focused, family, and/or relationship based. National support for family based prevention efforts such as the Strengthening Family Program (Kumpfer 1998) and collaborative community supported programs like the Healthy Families Initiative (Turner et al 2009) may aid stalking prevention efforts. These findings also support the need to bring relationship enhancement programs, such as Building a Lasting Love, to high-risk youth (LanghinrichsenRohling and Turner 2011).…”
Section: Gender and Stalking Theory Developmentmentioning
confidence: 99%
“…This measure has utility in guiding assessment and treatment planning as well as measuring outcomes. 10 The NCFAS-G includes eight domains that look at the family as a whole in terms of environment, parental capabilities, family interactions, family safety, child wellbeing, social/community life, self-sufficiency, and family health. These domains include a total of 58 subscales.…”
Section: Methodsmentioning
confidence: 99%
“…This measure has utility in guiding assessment and treatment planning as well as measuring outcomes. 10…”
Section: Methodsmentioning
confidence: 99%